2012
DOI: 10.2110/jsr.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Reactive transport modeling of brine reflux: dolomitization, anhydrite precipitation, and porosity evolution

Abstract: Both geothermal convection and brine reflux drive circulation of sea-water-derived fluids through carbonate platforms during early burial, but dynamic interactions between heat and solute transport and resulting diagenesis are at present poorly understood. This paper describes high-resolution reactive transport model (RTM) simulations that suggest that reflux of 85 ppt brines rapidly restricts geothermal convection to the platform margin, with flow focused in the more permeable shallow carbonates. In a baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 56 publications
10
92
1
Order By: Relevance
“…The ge om e try of re place ment do lo mite bod ies can be com plex, as this is a direct im age of the ge om e try of dolomitising fluid flow paths (Wilson et al, 1990) that in turn is con trolled by the prox im ity to the brine source, zones of rel a tively higher po ros ity, and per me ability con trasts, as in di cated by Gar cia-Fresca et al (2012) for the Perm ian San Andres For ma tion (cf. Al-Helal et al, 2012). In ad di tion, com plex lime stone-do lo mite dis tri bu tion as ob served in the Zechstein Lime stone reefs re sulted from mul ti ple reflux events, both in time and space (cf.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…The ge om e try of re place ment do lo mite bod ies can be com plex, as this is a direct im age of the ge om e try of dolomitising fluid flow paths (Wilson et al, 1990) that in turn is con trolled by the prox im ity to the brine source, zones of rel a tively higher po ros ity, and per me ability con trasts, as in di cated by Gar cia-Fresca et al (2012) for the Perm ian San Andres For ma tion (cf. Al-Helal et al, 2012). In ad di tion, com plex lime stone-do lo mite dis tri bu tion as ob served in the Zechstein Lime stone reefs re sulted from mul ti ple reflux events, both in time and space (cf.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Here the sharp fronts are again developed perpendicular to fluid flow, forming halos around fractures. Some previous RTM studies invoke a rather higher dolomite rate compared to that suggested by Arvidson and Mackenzie (1999) and used in most previous RTM simulations of dolomitisation (Jones and Xiao, 2005;Al-Helal et al, 2012;. The use of a faster kinetic rate results in sharp dolomite fronts (Consonni et al, 2010).…”
Section: Fault-controlled Dolomitisation and Htd Geobodiesmentioning
confidence: 98%
“…RTM has already been extensively applied to study the formation of dolomites in low-temperature shallow reflux systems (Jones and Xiao, 2005;Garcia-Fresca et al, 2009;Al-Helal et al, 2012;Xiao et al, 2013;Lu and Cantrell, 2016), as well as during burial diagenesis by fluids circulating due to geothermal convection (Wilson et al, 2001;Whitaker and Xiao, 2010) and sedimentary compaction (Consonni et al, 2010;Frazer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These dense brines are potential dolomitizing fluids that can descend into underlying pore networks under the influence of gravity. However, the flow of diagenetic fluids critically depends on spatial variations in the permeability, generating complex dolomite bodies at a range of scales (Al-Helal et al 2012). Intervals of peritidal cycles dominated by dolomite are abundant in the areas of regional highs and on the inner platform during regressive periods, whereas limestone-rich cyclic intervals develop best near depocenters during transgression periods .…”
Section: Hydrology Of the Dolomitizing Fluidsmentioning
confidence: 99%